2016
DOI: 10.1016/j.conbuildmat.2016.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimisation of phase change material-impregnated lightweight aggregates for geopolymer composites made from aluminosilicate rich mud and milled glass powder

Abstract: h i g h l i g h t sPCM vacuum impregnation is very successful for expanded clay lightweight aggregate. Polyester resin coating is able to retain all of the impregnated PCM from leakage. Resin coating is chemically stable and neutral, also improving thermal conductivity. Novel combination of geopolymer and thermal energy storing aggregates evaluated. ME-LWA has a high energy storage capacity of 157 J/g. a r t i c l e i n f o a b s t r a c tMacro-encapsulated aggregates (ME-LWAs) consisting of expanded clay lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…Concrete samples containing GFG showed no major change in workability compared to control samples. [168][169][170][171][172][173][174] Similar findings were also observed in other studies, indicating that the use of foam glass could adversely affect the properties of lightweight concrete due to ASR expansion.…”
Section: Glass-based Productssupporting
confidence: 86%
See 1 more Smart Citation
“…Concrete samples containing GFG showed no major change in workability compared to control samples. [168][169][170][171][172][173][174] Similar findings were also observed in other studies, indicating that the use of foam glass could adversely affect the properties of lightweight concrete due to ASR expansion.…”
Section: Glass-based Productssupporting
confidence: 86%
“…Similarly, other studies have also demonstrated that glass-rich geopolymers prepared by coupling CWG and other wastes could potentially be used in a variety of civil engineering applications. [168][169][170][171][172][173][174]…”
Section: Glass-based Productsmentioning
confidence: 99%
“…Lightweight polymer matrix composites coupling structural or semistructural functions and TES capability could be successfully applied where weight and volume savings need to be combined with precise temperature control. Even though several papers have recently been published on encapsulated and shape‐stabilized PCMs in various polymer matrixes, only a few papers dealing with the development of structural composites with TES capability can be found. The major parts of the scientific reports deal with sandwich structures for thermal management with or without the introduction of a PCM.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such fields can be the automotive, aerospace, portable electronics and technical garments industries. However, even though there are many examples in the literature of encapsulated and shape stabilized PCMs embedded in a polymer matrix [5,12,17,29,[39][40][41][42], only few papers can be found that deal with the development of polymer composites merging structural and TES functions. Most of the examples of such composites regard sandwich structures that have functions of thermal management with [22] or without [43,44] the use of a PCM.…”
Section: Introductionmentioning
confidence: 99%